Literature the People Love Reading Chinese Texts from the Early Maoist Period (1949–1966) - Fleit Hang, Krista Van. (Chinese Literature and Culture in the World, 2013)
Examining the production of 'people's literature' in China, this study provides a new interpretive framework with which to understand socialist literature and presents a sympathetic understanding of culture from a period in China's history in which people's lives were greatly and obviously affected by political events.